2017 IEEE International Conference on Image Processing (ICIP) 2017
DOI: 10.1109/icip.2017.8296389
|View full text |Cite
|
Sign up to set email alerts
|

DenseNet for dense flow

Abstract: Classical approaches for estimating optical flow have achieved rapid progress in the last decade. However, most of them are too slow to be applied in real-time video analysis. Due to the great success of deep learning, recent work has focused on using CNNs to solve such dense prediction problems. In this paper, we investigate a new deep architecture, Densely Connected Convolutional Networks (DenseNet), to learn optical flow. This specific architecture is ideal for the problem at hand as it provides shortcut co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(97 citation statements)
references
References 26 publications
1
96
0
Order By: Relevance
“…Compared to unsupervised optical flow learning, the advantage of our learned conditional prior becomes obvious. Although DenseNetF [40] and UnFlowC [27] employ more powerful network structures than FlowNetS, their EPEs on MPI-Sintel Test are still 1.5 higher than our CPNFlow. Note that in [27], several versions of result are reported, e.g.…”
Section: Benchmark Resultsmentioning
confidence: 84%
“…Compared to unsupervised optical flow learning, the advantage of our learned conditional prior becomes obvious. Although DenseNetF [40] and UnFlowC [27] employ more powerful network structures than FlowNetS, their EPEs on MPI-Sintel Test are still 1.5 higher than our CPNFlow. Note that in [27], several versions of result are reported, e.g.…”
Section: Benchmark Resultsmentioning
confidence: 84%
“…Upsampling cell. Several hand-designed encoderdecoder architectures have emerged [2,27,73,76] which incorporate the above architecture design choices. Typically such methods propose decoding modules which apply architectural blocks (ShuffleNet [72], DenseNet [31] block, etc).…”
Section: Darts For Dense Predictionmentioning
confidence: 99%
“…The first attempt of a deep optical flow estimation network, FlowNet [17], proposed two networks, namely FlowNetS and FlowNetC, and greatly improved the runtime of previous work. Zhu et al [18] developed an optical flow estimation method called DenseNet by extending a deep network for image classification, and demonstrated that it outperforms other unsupervised methods. FlowNet 2.0 [19] is a follow-up paper of FlowNet [17].…”
Section: Optical Flow Estimationmentioning
confidence: 99%
“…Therefore, we can expect that a better understanding of the images results in a more accurate matching. As shown in [18], in optical flow estimation, feature extractors trained on image classification tasks are recommendable for unsupervised learning.…”
Section: A Stronger Feature Extractorsmentioning
confidence: 99%